Opposition to Jehovah’s Witnesses in Russia: Legal Measures - Fautré, Willy (The journal of CESNUR, 2020)
Jehovah’s Witnesses in Russia have faced increasing hostility from the state and the Russian Orthodox Church since the late 1990s, as legislation designed to safeguard the country against violent extremist ideologies and terrorism has instead been instrumentalized to persecute peaceful “non-traditional” religious minorities. For years, Jehovah’s Witnesses have been stigmatized and cast as a threat to the Russian national and religious identity. Now, controversial legislative changes have allowed for Jehovah’s Witnesses to be labelled “extremist” and formally prosecuted on the grounds of amended anti-extremism laws. This paper highlights how Putin’s political concept of “spiritual security” has driven the legal dynamic leading to the criminalization of the legitimate exercise of the right to religious practices over the last 20 years. It exposes the common agenda of the Russian Orthodox Church, the Russian anti-cult movement led by Alexander Dvorkin, and the Russian government, aimed at the elimination of Jehovah’s Witnesses and other religious minorities. It analyses the successive laws adopted to this end by the Russian Parliament after immense pressure from these actors. It documents the alarming escalation of human rights violations against Jehovah’s Witnesses, which include arrests, administrative fines, pretrial detention, and prison sentences, as well as a legal ban and seizures of all their property. It concludes with some encouraging signs of advocacy from the US government, and some faith in the capacity of Jehovah’s Witnesses to survive this repression.